Students’ Perceptions toward Using Charlie Puth Songs in the Album ’Some Type of Love’ in Mastering Vocabulary at the Eighth Grade of SMP Barata Semagung in the Academic Year of 2024/2025 - Fathonah, Nimas Ayu; Setiyono, Junaedi; Widodo, Sri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Vocabulary mastery is a fundamental aspect of English learning but remains a major challenge for junior high school students. Traditional methods such as memorizing word lists are often seen as monotonous and ineffective. This study explores students perceptions toward the use of songs from Charlie Puths ’Some Type of Love’ album in supporting English vocabulary acquisition. A qualitative approach with a phenomenological method was employed, involving 21 eighth-grade students at SMP Barata Semagung in the academic year 2024/2025. Data were collected throught a Likert-scale questionnaire and semi-structured interviews. The findings reveal that the songs made learning more enjoyable, helped them understand and remember vocabulary more easily, and increased their confidence in speaking English. Although some found the songs unfamiliar, student responded positively and emphasized the need visual aids such as lyrics or video clips. These study contributes to English language pedagogy by proposing music-based vocabulary instruction as an engaging alternative for junior high school learners. Therefore, the implementation of songs in English learning is recommended to be contextual and supported by appropriate multimedia tools.